Study On Post Mortem Incidence And Pathology Of Colisepticemia Of Young Broiler Chicks In Odisha - Behera, Debasish; Samal , Ashabaree (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Post mortem on 4771 chicks within the age group of one to three weeks formed the basis of this study. The disease conditions were categorized as omphalitis, colibacillosis, enteritis, debility, salmonellosis, coccidiosis, gout, aspergillosis, hepatitis, nephritis, pneumonia, and IBD. The highest post mortem cases were of colibacillosis; of which omphalitis was 20.4% followed by colicepticemia (17.6%) and enteritis (10.5%). Out of total bacterial isolates 72% were positive for Escherichia coli and rest 25 to 30% isolates were belonged to the genera Proteus, Salmonella, Pseudomonas, Staphylococcus, Streptococcus, Klebsiella and Enterobacter. E. coli was serotyped as O1, O119 and O57. On antibiotic sensitive test these were found to be highly sensitive to Ciprofloxacin, Norfloxacin, Chloramphenicol and Furazolidone.
Keywords: Mortality; Colisepticaemia; Escherichia coli; Omphalitis; Serotype